Serum levels of lamotrigine during delivery in mothers and their infants - Kacirova, Ivana; Grundmann, Milan; Brozmanova, Hana (Epilepsy research, 2010)
PURPOSE: We followed up lamotrigine transport through the placenta and analyzed maternal and umibilical cord concentrations, its ratio and maternal lamotrigine clearance in monotherapy and in combinations. METHODS: Maternal and umbilical cord concentrations were analyzed during delivery in a cohort of 63 women between 2001 and 2009. The request forms for routine therapeutic drug monitoring were used as the data source. Maternal concentrations were used for the estimation of apparent oral clearance and paired infant and maternal concentrations for estimation of the infant (umibilical cord)/maternal serum concentration ratio. RESULTS: The lamotrigine infant/maternal serum concentration ratio ranged in monotherapy from 0.40 to 1.38 (median 0.91). The ratio in monotherapy showed a possible distribution to two subgroups. Concomitant administration of valproic acid significantly increased both maternal and infant lamotrigine concentrations and significantly decreased lamotrigine clearance by about 65%. Co-medication with carbamazepine increased lamotrigine clearance non-significantly. Highly significant correlations were found between maternal and umbilical cord lamotrigine concentrations, both in monotherapy and in the lamotrigine+valproic acid combination. Infant concentrations of valproic acid were found to be about 30% higher and infant concentrations of carbamazepine were found to be about 20% lower than maternal concentrations. CONCLUSIONS: Our data from the large cohort showed the interindividual variability of umbilical cord/maternal serum concentration ratio in lamotrigine monotherapy caused probably by the different activity of the placental lamotrigine metabolizing enzymes UGT1A4 and 2B7 associated with genetic polymorphism. The potential teratogenic effect of lamotrigine combination with valproic acid could be associated with the higher lamotrigine and valproic acid concentrations in the fetus.
Keywords: triaziny; Delivery, Obstetric; Epilepsy; epilepsie; Retrospective Studies; těhotenství; mladiství; Cohort Studies; Lamotrigine; lamotrigin; mužské pohlaví; Fetal Blood; Adult; mladý dospělý; kohortové studie; Triazines; vedení porodu; Infant, Newborn; Maternal-Fetal Exchange; Young Adult; ženské pohlaví; novorozenec; retrospektivní studie; Humans; Pregnancy; dospělí; Female; fetální krev; Adolescent; maternofetální výměna látek; lidé; Male